2016
DOI: 10.4137/bcbcr.s32792
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in the Bahamas in 2009–2011

Abstract: BACKGROUNDBreast cancer is the most common form of cancer affecting women in the Bahamas, which consists of many islands. This is the first attempt to identify which island has the highest occurrence of breast cancer.OBJECTIVEThe aim of this study was to describe the sociodemographical and spatial features of breast cancer in the Bahamas in 2009–2011.METHODSA review of the medical records of all women with a confirmed diagnosis of breast cancer during the period January 1, 2009–December 31, 2011, was undertake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Eighteen publications described clinicopathologic features of women from seven Caribbean countries (the Bahamas, Cuba, Guadeloupe, Jamaica, Puerto Rico, Suriname, and Trinidad). 51-67,105 The most common histologic type was infiltrating ductal carcinoma. For countries that reported staging data, stage ≥ 2 at presentation was reported in the Bahamas, 51 Jamaica, 54,56 and Trinidad.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen publications described clinicopathologic features of women from seven Caribbean countries (the Bahamas, Cuba, Guadeloupe, Jamaica, Puerto Rico, Suriname, and Trinidad). 51-67,105 The most common histologic type was infiltrating ductal carcinoma. For countries that reported staging data, stage ≥ 2 at presentation was reported in the Bahamas, 51 Jamaica, 54,56 and Trinidad.…”
Section: Resultsmentioning
confidence: 99%
“…51-67,105 The most common histologic type was infiltrating ductal carcinoma. For countries that reported staging data, stage ≥ 2 at presentation was reported in the Bahamas, 51 Jamaica, 54,56 and Trinidad. 67 In contrast, one study in Puerto Rico reported that 88.9% of patients presented with stage I to III and T1/T2 BC.…”
Section: Resultsmentioning
confidence: 99%
“…The high heterogeneity in this analysis was explained by the type of study, with studies that used consecutive sampling presenting a higher proportion of late-stage diagnosis than population-based studies. Only four population-based studies with 837 women were included, and of those, two were the single representatives of their countries (Barbados [32] and Bahamas [33]), and the other two were one of two studies included from Argentina [34] and Cuba [30]. Other variables likely to be related to the stage at diagnosis, such as school years, socioeconomic status and race, could not be evaluated because few studies reported them to allow comparability.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the interest indicated by females for the medical items in this study (e.g. cancer, infectious diseases, and reproductive health) mirror both past and present clinical issues experienced by Bahamian women (Cox, 1997;Figueroa, 2014;Mungrue et al, 2016;Trottier et al, 2016). This finding coupled with Ainsley and Ainsley's (2011b) scholarship indicates that further research is warranted to understand how The Bahamas' history and culture uniquely contribute to girls' perceptions of and interests in these specific areas of human biology and medicine, and why physical science and technology (preferred by their male counterparts) are largely eschewed by female Bahamian students.…”
Section: Discussionmentioning
confidence: 58%